Psychological Influences on Bus Travel Mode Choice: A Comparative Analysis between Two Chinese Cities - Jian Chen; Qi Chen; He-ping Li (Journal of Advanced Transportation)
Psychological factors give an important influence on the behavior of travel mode choice, but the effects vary from different cities. To identify and explain the differences, this study makes a comparative analysis between two Chinese cities, Chongqing and Chengdu: a typical mountain city and a typical plain city. The sample is obtained by questionnaires containing 401 and 450 valid records of the two cities, respectively. The model used in this study is established based on the framework of the theory of planned behavior. The main work of this study has three aspects: (1) define the measured variables based on the combination of bus travel characteristics and the theory of planned behavior; (2) verify the model validity in both two cities; (3) make a comparative analysis on the two cities. According to the results, the validity of the theory framework and measured variables is verified; the perceived behavioral control plays the most important role in affecting the behavior of traveling by bus in both two cities; significant differences between the two cities are presented and explained.